Some features of the development and construction of finite-difference models of rod structures of radio-electronic means - E. A. Danilova; G. V. Tankov; N. K. Yurkov (Вестник Дагестанского государственного технического университета: Технические науки, 2022)
Objective. The aim of the study is to build finite-difference models that can be used to test the bending vibrations of a rod under various fastening conditions, solving the problem in the frequency or time domain. Method. The study is based on the application of the finite difference method and the finite element method. Result. The necessity of application is substantiated and the technique of mathematical modeling is proposed for the design engineering of radio-electronic means operating under conditions of dynamic external influences. The significance of the use of discrete models and the peculiarities of their creation for studying the dynamics of certain constructs of electronic equipment are analyzed. The concept of studying simple models of bar structures for the analysis and verification of the theoretical positions of constructing models of structures is proposed. The features in the development of models for the calculation of natural shapes and frequencies of bending vibrations of rods are shown. Conclusion. Assessment of vibration strength and vibration resistance of non-stationary structures of radio-electronic means is possible by methods and means of mathematical modeling used as test models to test various hypotheses and theoretical positions in the study of the dynamics of complex structures and the design of radio-electronic means.